2020
DOI: 10.1007/s43188-020-00056-z
|View full text |Cite
|
Sign up to set email alerts
|

A history of the roles of cytochrome P450 enzymes in the toxicity of drugs

Abstract: The history of drug metabolism began in the 19th Century and developed slowly. In the mid-20th Century the relationship between drug metabolism and toxicity became appreciated, and the roles of cytochrome P450 (P450) enzymes began to be defined in the 1960s. Today we understand much about the metabolism of drugs and many aspects of safety assessment in the context of a relatively small number of human P450s. P450s affect drug toxicity mainly by either reducing exposure to the parent molecule or, in some cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 191 publications
(208 reference statements)
1
57
0
Order By: Relevance
“…The CYP super protein family has >300,000 members that are involved, among others, in the biosynthesis of steroids, fatty acids and natural products as well as in the degradation of drugs in humans and of xenobiotics in the environment. 41,42 Thus this is an important enzyme class with relevant applications in biocatalysis, biomedicine, pharmacology, toxicology and biotechnology [42][43][44] . Previously, we achieved the stereoselective and regioselective hydroxylation of testosterone (1) by evolving the self-sufficient Bacillus megaterium cytochrome P450 BM3 monooxygenase 40 .…”
Section: Resultsmentioning
confidence: 99%
“…The CYP super protein family has >300,000 members that are involved, among others, in the biosynthesis of steroids, fatty acids and natural products as well as in the degradation of drugs in humans and of xenobiotics in the environment. 41,42 Thus this is an important enzyme class with relevant applications in biocatalysis, biomedicine, pharmacology, toxicology and biotechnology [42][43][44] . Previously, we achieved the stereoselective and regioselective hydroxylation of testosterone (1) by evolving the self-sufficient Bacillus megaterium cytochrome P450 BM3 monooxygenase 40 .…”
Section: Resultsmentioning
confidence: 99%
“…39 High frequency of polymorphic P450 express in black led to high toxicity and unexpected drug interactions through drug metabolism. 15,39 It interacts with vincristine, platinum containing agents and bortezomib which can exacerbate its neurotoxicity. 40 Besides, it has also been documented to enhance the sedative effect of barbiturates, alcohol, chlorpromazine and reserpine.…”
Section: Drug Interaction and Toxicity Of Thalidomidementioning
confidence: 99%
“…Studies have shown that thalidomide can increase the production of oxygen free radicals and induce oxidative stress. 14,15…”
Section: Introductionmentioning
confidence: 99%
“…Medications administered concurrently that are substrates for the same cytochrome enzyme overwhelm the metabolic capacity of the cytochrome and interfere with efficacy or may result in toxicity [ 45 ]. If two drugs have the same affinity for an enzyme, they become competitive inhibitors in a dose related way [ 49 ]. If one of the drugs is a substrate for another cytochrome P450 enzyme with less affinity, metabolism may be shunted toward those less preferred pathways.…”
Section: Discussionmentioning
confidence: 99%